Morphology and molecular phylogeny of Macrobrachium snpurii, a new species of the genus Macrobrachium Bate, 1868 from Kerala, India - Pillai, P. M.; Unnikrishnan, V. (Zootaxa, 2013)
Macrobrachium snpurii sp. nov., collected from the Karamana River, in the lower reaches of Western Ghats, is described and illustrated. DNA barcoding using Cytochrome B gene sequences has elucidated the taxonomic status of the new spe-cies and the NJ tree reveals that M. snpurii sp. nov., is phylogenetically close to M. idella idella. However, morphometric and meristic features of the species share certain characters with M. idella idella, M. patheinense and M. tratense, while it diverges remarkably from these three species in distinctive diagnostic characters: rostral formula 12–14/4 with 2 pos-torbital teeth; carapace smooth with distal end of rostrum directed upwards; chelae with 2 proximal denticles both in the movable and immovable fingers. A wide gap present in the distal part of the chelae, when fingers are closed. Movable finger, longer than the immovable and distal end of fingers inwardly hook-like; palm more pigmented than fingers and telson extends beyond the level of the outer lateral spine of uropodal exopod. A pair of plumose setae is present between the inner pair of movable spines of telson.